Teachers’ perceptions on the causes of poor academic performance of grade 12 learners in four selected schools in the Zambezi Region of Namibia - Maemeko, E.L.; Nkengbeza, D.; Ntabi, M.L. (IJRDO- Journal of Educational Research, 2017)
Grade 12 leaners in most Senior Secondary Schools in the Zambezi Region of Namibia continueto perform poorly in both the International General Certificate of Secondary Education (IGCSE)and the Higher International General Certificate of Secondary Education (HIGCSE) finalexamination. The purpose of this study is to investigate the poor academic performance of thegrade 12 learners in four selected Senior Secondary Schools in two circuits in the Zambezi Regionof Namibia. The main research question is: What are the main causes of the low academicperformance in the selected schools? Qualitative research method was used in this study. Thestudy involves four Senior Secondary Schools with five teachers from each School including theirprincipals and one deputy principal or head of department. Two of the four schools were from arural area and the other two were from an urban area. The data was collected using interviewsand document review. The analysis consisted of coding and then categorizing data intomanageable themes, identifying and isolating what was important to note, what we learned andwhat we could report on in this research. Our findings are that among factors that might havecaused the poor academic performance of grade 12 learners in the four selected schools are: lackof discipline in schools, learners lack motivation, English as a medium of instruction, poorlearning environment, learners’ admission level coupled with limited support from parents,unqualified subject teachers and lack of teaching-learning resources among others.